2017
DOI: 10.1159/000456063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Umbilical Serum Copeptin Relative to Erythropoietin and S100B as Asphyxia Biomarkers at Birth

Abstract: Background: Birth asphyxia, estimated to account for a million neonatal deaths annually, can cause a wide variety of neurodevelopmental impairments. There is a need to develop new, swift methods to identify those neonates who would benefit from neuroprotective treatments such as hypothermia. Objectives: To examine the utility of cord serum copeptin, a stable byproduct of arginine vasopressin release, as a biomarker of birth asphyxia based on a comparison with 2 biomarkers of hypoxia and brain trauma: erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Unfortunately, we did not have AVP samples available before 1 h and therefore our AVP measurements were taken a mean of 30 min after the peak appearance of sinusoidal activity, potentially reducing the strength of the relationship. Nonetheless, AVP levels 1 h after HI were strongly associated with loss of EEG power by day 3 (r 2 = 0.61), consistent with clinical studies suggesting that AVP or its more stable co-metabolite copeptin may have value as a standalone biomarker for HIE (Evers & Wellmann, 2016;Summanen et al 2017). Further studies are needed to understand the relationship between AVP levels after HI and neural injury.…”
Section: Figure 3 Spectral Power and Sample Entropy Of Fetal Heart Rsupporting
confidence: 90%
See 1 more Smart Citation
“…Unfortunately, we did not have AVP samples available before 1 h and therefore our AVP measurements were taken a mean of 30 min after the peak appearance of sinusoidal activity, potentially reducing the strength of the relationship. Nonetheless, AVP levels 1 h after HI were strongly associated with loss of EEG power by day 3 (r 2 = 0.61), consistent with clinical studies suggesting that AVP or its more stable co-metabolite copeptin may have value as a standalone biomarker for HIE (Evers & Wellmann, 2016;Summanen et al 2017). Further studies are needed to understand the relationship between AVP levels after HI and neural injury.…”
Section: Figure 3 Spectral Power and Sample Entropy Of Fetal Heart Rsupporting
confidence: 90%
“…Nonetheless, AVP levels 1 h after HI were strongly associated with loss of EEG power by day 3 ( r 2 = 0.61), consistent with clinical studies suggesting that AVP or its more stable co‐metabolite copeptin may have value as a standalone biomarker for HIE (Evers & Wellmann, ; Summanen et al . ). Further studies are needed to understand the relationship between AVP levels after HI and neural injury.…”
Section: Discussionmentioning
confidence: 97%
“…Umbilical cord serum EPO levels did not correlate with the duration of the labor nor that of the second stage of the labor in the current study. This is consistent with the findings of a recent study on term asphyxiated neonates [15].…”
Section: Commentsupporting
confidence: 93%
“…Higher S100B concentrations were associated with cord blood acidosis, aEEG pattern severity, HIE severity, and correlated with neurodevelopmental sequelae at 6-year follow-up and death) [62]. In contrast, Summanen et al found cord blood S100B to be a poor NB of PA in term newborns [63] (Table 2).…”
Section: Bloodmentioning
confidence: 95%